Weak Solutions of a Reaction Diffusion System with Superdiffusion and Its Optimal Control (Journal of Nonlinear Modeling and Analysis, 2024)
The existence and uniqueness of weak solutions to the 2-dimensional reaction diffusion system with superdiffusion and the optimal control of such model are investigated in this paper. Fractional function spaces, Galerkin approximation method and Gronwall inequality are used to obtain the existence and uniqueness of weak solutions. On this basis, an optimal control problem of such superdiffusive system is further considered by using the minimal sequence.
Keywords: Weak solutions; optimal control; reaction-diffusion; Riesz operator.